ANALISIS PENGARUH VARIABEL JAM KERJA, PENDIDIKAN TINGGI, UPAH DAN PDRB TERHADAP TINGKAT PARTISIPASI ANGKATAN KERJA MUDA DI INDONESIA - Erhaenis Yuliana (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
This study aims to determine the factors that influence the Youth Labor Force Participation Ratein Indonesia. This research is a research obtained through intermediary media or indirectly with adescriptive quantitative approach, so that the data used are data from 34 Indonesian provincesfrom the Statistics Indonesia from 2010-2017. The analysis technique used is panel data analysiswith the Eviews 6.0 application. The dependent variable in this study is the Youth Work ForceParticipation Rate in Indonesia, while the independent variables are Working Hours, HigherEducation, Wages and GRDP. The results of this study indicate that wages have a positive andsignificant effect on the Youth Work Force Participation Rate in Indonesia, and GRDP has anegative but significant effect on the Youth Labor Force Participation Rate in Indonesia. ForHigher Education there is a positive but not significant effect on the Youth Labor ForceParticipation Rate in Indonesia, and for Working Hours has a negative and not significant effecton the Youth Labor Force Participation Rate in IndonesiaKeywords: Youth Labor Force Participation Rate in Indonesia, Working Hours, Higher Education, Wages, GRDP